Beta2-adrenergic receptor polymorphisms among healthy Jordanian population (Pharmacy Practice, 2024)
Background: Several polymorphisms of the β2-adrenergic receptor gene have been identified. These polymorphisms affect receptor function and significantly reduce expressed receptors in the cells. The main objective of this study is to determine the frequency of β2 adrenergic receptor polymorphism among a healthy Jordanian population and compare it with those of different ethnic groups. Blood samples were collected from 96 healthy Jordanians. β2-adrenergic receptor gene polymorphism at codon 16 and codon 27 was assessed by Polymerase Chain Reaction (PCR) followed by Restriction Fragment Length Polymorphism RFLP. The minor allele frequency of β2-adrenergic receptor polymorphism at position 46 (46 G/A) was 31%, while the polymorphism at position 79 (79 C/G) was 14% in the Jordanian population. The genotype frequencies for 46 (46 G/A) were 51% for (GG), 13% for (AA) and 36% for (GA). In case 79 C/G, the genotype frequencies were 87.5% 7.3 % 5.2% CC, GG and CG genotypes, respectively. This study’s results indicate marked interethnic differences in the genotype and allele frequencies of the two β2-adrenergic receptor polymorphisms among healthy Jordanians, Caucasians, African Americans, and Asians.